SPATIAL DISTRIBUTION OF MICROBIAL METHANE PRODUCTION PATHWAYS IN TEMPERATE ZONE WETLAND SOILS: STABLE CARBON AND HYDROGEN ISOTOPE EVIDENCE - Hornibrook E.R.C.; Longstaffe F.J.; Fyfe W.S. (My University, 1997)
The identity and distribution of substrates that support CH4 production in wetlands is poorly known at present. Organic compounds are the primary methanogenic precursor at all depths within anoxic wetland soils; however, the distribution of microbial processes by which these compounds are ultimately converted to CH4 is uncertain. Based on stable isotope measurements of CH4 and ΣCO2 extracted from soil porewaters in two temperate zone wetlands, we present evidence that a systematic spatial distribution of microbial methanogenic pathways can exist in certain anoxic, organic-rich soils. CH4 production by the acetate fermentation pathway is favored in the shallow subsurface, while methanogenesis from the reduction of CO2 with H2 becomes more predominant in older, less reactive peat at depth. This distribution can account for many of the reported CH4 emission characteristics of wetlands, in particular, their sensitivity to changes in primary productivity, temperature, and hydrology. These factors play an important role in controlling the short-term supply of labile substrates to fermentive methanogens in the shallow subsurface where the most intense CH4 production occurs. Predominance of the CO2-reduction pathway at depth may help to explain reports of CH4 with a semifossil age in lower peat layers.